1993
DOI: 10.1128/mcb.13.12.7813-7825.1993
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Binds to a Family of E2F Transcription Factors

Abstract: E2F is a transcription factor that helps regulate the expression of a number of genes that are important in cell proliferation. Recently, several laboratories have isolated a cDNA clone that encodes an E2F-like protein, known as E2F-1. Subsequent characterization of this protein showed that it had the properties of E2F, but it was difficult to account for all of the suggested E2F activities through the function of this one protein. Using low-stringency hybridization, we have isolated cDNA clones that encode tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…E2F2, E2F3, E2F4 and E2F5 members contain Rb1-binding domains similar to E2F1 and interact with Rb1 [48,49]. The interaction of Rb1 with E2F2 and E2F3 results in blockage of their pro-proliferative function, which is consistent with their established role as transcriptional activators [48,50]. However, E2F4 and E2F5 are considered transcriptional repressors and therefore the function of their interaction with Rb1 is different.…”
Section: E2f-dependent Signalingmentioning
confidence: 81%
“…E2F2, E2F3, E2F4 and E2F5 members contain Rb1-binding domains similar to E2F1 and interact with Rb1 [48,49]. The interaction of Rb1 with E2F2 and E2F3 results in blockage of their pro-proliferative function, which is consistent with their established role as transcriptional activators [48,50]. However, E2F4 and E2F5 are considered transcriptional repressors and therefore the function of their interaction with Rb1 is different.…”
Section: E2f-dependent Signalingmentioning
confidence: 81%
“…Of particular interest to this study, the retinoblastoma tumor suppressor protein (pRb) suppresses the G1/S phase transition. In quiescent neurons, hypophosphorylated pRb represses members of the E2F protein family to block cell cycle progression ( Lees et al., 1993 ). In response to a mitogenic stimulant, D-type cyclins are synthesized and bind to Cdk4 or Cdk6.…”
Section: Discussionmentioning
confidence: 99%
“…63 , 64 Alterations in Na + -K + -ATPase activity also represent an important mechanism of diabetics-induced neurotoxicity. 65 In the same vein, nitric oxide, as a neurotransmitter, is reported to mediate synaptic activity, neural plasticity, and memory function. 66 Interestingly, we found that treatment with AESTL reverses the overexpression of Na + -K + -ATPase, COX-2 and NO to the baseline value, hence suggesting the anti-inflammatory and therapeutic role of AESTL in the maintenance of ion gradients across biological membranes and thus confer significant protection to the brain by stabilizing the functional integrity of the membrane.…”
Section: Discussionmentioning
confidence: 99%